TB-08 PATIENT DERIVED XENOGRAFT'S BIOBANK FROM KANSAI MOLECULAR DIAGNOSIS NETWORK FOR CENTRAL NERVOUS SYSTEM TUMORS. (16th December 2019) - Kijima, Noriyuki; Kanematsu, Daisuke; Shofuda, Tomoko; Nonaka, Masahiro; Iwata, Ryoichi; Fukai, Junya; Inoue, Akihiro; Sasayama, Takashi; Tsuyuguchi, Naohiro; Kawashima, Toshiyuki; Higuchi, Yuichiro; Suemizu, Hiroshi; et al.
Abstract: Patient-derived xenografts (PDXs) are essential tools for translational research for brain tumors. However, it is sometimes difficult for each institution to establish PDXs because it needs experiences and techniques and it also takes a lot of works to establish them. Thus we aim to establish patient derived xenograft's biobank among institutions of Kansai Molecular Diagnosis Network for Central Nervous System (CNS) Tumors, Osaka, Japan. We have already began sharing two anaplastic astrocytoma PDXs, twelve glioblastoma IDH wild type PDXs, two medulloblastoma Shh subgroup PDXs, one atypical teratoid/rhabdoid tumor (AT/RT) PDX, and three metastatic brain tumor PDXs. Furthermore these PDXs can also be cultured in vitro, except 2 medulloblastoma SHH subgroup PDXs, 1 AT/RT PDX. However, we have not yet established any PDXs from low grade glioma, ependymoma, primary central nervous system lymphoma (PCNSL), diffuse intrinsic pontine glioma (DIPG). We began sharing these PDXs among the institutions of Kansai Molecular Diagnosis Network for CNS Tumors, Osaka, Japan. However, further improvement is necessary to succeed in establishing PDX from low grade glioma, PCSNL, DIPG, etc. and get enough number of PDXs so we can share PDXs from almost all of the brain tumors.